2017
DOI: 10.1680/jinam.16.00020
|View full text |Cite
|
Sign up to set email alerts
|

What does NDE need to achieve for cast iron pipe networks?

Abstract: Grey cast iron water pipe networks have been installed around the world, often 100-180 years ago. Cohorts (which can be defined by age, size, casting technology and geographical location, to specify but a few groups) degrade at different rates due to environmental and in-service issues, which can lead to a significant loss in mechanical performance. Hence, the management of these assets can be extremely problematic in terms of identifying priorities. The current paper considers the causes of such degradation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The damage stages and median m obs values appear to be correlated, but the m obs value is so low, even in the sound state. Thus, improved nondestructive testing methods may be more beneficial for identifying the damage states of buried pipes [139].…”
Section: Gmentioning
confidence: 99%
“…The damage stages and median m obs values appear to be correlated, but the m obs value is so low, even in the sound state. Thus, improved nondestructive testing methods may be more beneficial for identifying the damage states of buried pipes [139].…”
Section: Gmentioning
confidence: 99%
“…Previous work has shown that non-destructive evaluation, NDE is likely to be of limited use if taken as the only measure of assessment (Rainer et al, 2017). The anisotropic nature of grey cast iron due to the graphite flake distribution, orientation and size is one of the main Accepted manuscript doi: 10.1680/jinam.21.00019 8 hurdles in the development of a consistent and reliable NDE method.…”
Section: Introductionmentioning
confidence: 99%
“…Routine and yet effective condition assessment of these buried pipes can minimise the negative consequences of deterioration in the utility network. To further minimise the risk of damaging the utility network adopting non-destructive technologies (NDT) for assessment would be ideal as they have the potential for providing routine and effective assessment with minimum disruption (Roberge, 2007;Rainer et al, 2017). Geophysical techniques, such as Ground Penetrating Radar (GPR), have been utilised to locate and map cast iron pipes (Mooney et al, 2010;Pennock et al, 2010;Ayala-Cabrera et al, 2011) and assess their condition (Hao et al, 2012;Liu et al, 2012;Rogers et al, 2012;Liu and Kleiner, 2013) including determination of the corroded state of cast iron pipes.…”
Section: Introduction 76mentioning
confidence: 99%